JURIDICAL STUDIES ON SUBSTANCE AND PROCEDURE OF THE DISMISSAL OF THE PRESIDENT AND/OR VICE-PRESIDENT AFTER THE REFORMATION - Siti Rodhiyah Dwi Istinah (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Reformation era was proclaimed by the amendment of the 1945 Constitution (UUD 1945) of the Republic of Indonesia which was done by MPR since 1999 until 2002. The changes obviously gives consequences in regards to the substance and procedure of accountability of the President and/or Vice-President which were distinctive from the previous one which can be explored in the formulation of the 1945 Constitution of the Republic of Indonesia. The selection of the governmental system of Presidential gave impact towards the characteristics of such system which banished the accountability of the President to the parliament (MPR). Although the state of the President was strong (fixed executive), the dismisal might probably happen during their tenure when the President and/or Vice-President violating the law. Key Words: the dismissal of the President and/or Vice-President, substance, procedure